Numerical Analysis of the energy loss mechanism in cavitation flow of a control valve. (August 2021) - Xu, Xiaogang; Fang, Liang; Li, Anjun; Wang, Zhenbo; Li, Shuxun
Highlights: Energy transfer and loss in cavitation flow of a control valve were studied. Gradient of flow energy was proposed to evaluate the rate of energy loss. Energy loss is composed by throttling loss and additional loss of cavitation. The additional energy loss of cavitation increases with severe cavitation. Abstract: Cavitation can cause considerable damage within control valves and nearby pipelines. Despite the extensive research, the mechanism of energy loss in cavitation flow of control valves is not yet adequately understood. In this study, the mechanism of mechanical energy transfer and loss in unsteady cavitation flow and the effect of cavitation on energy loss of a control valve with different pressure ratio conditions were numerically investigated by the validated numerical method based on the LES model. A dimensionless parameter called flow energy gradient was proposed to evaluate the rate of energy loss. Results show that the contribution of the energy loss is much greater in the region of valve seat throat where strong throttling and severe cavitation occur. The total energy loss in the control valve is composed by the throttling loss and the additional energy loss of cavitation, the latter leads to an increase in flow resistance and a decrease in flow capacity of the control valve. Moreover, the additional energy loss induced by cavitation increases with the severity of cavitation, which may result from the change of the liquid-vapor phase.